Comparison of proliferative activity of Wharton jelly mesenchymal stem cells in cultures under various gas conditions - Shuvalova, N.S.; Kordium, V.A. (Вiopolymers and Cell, 2015)
Aim. To optimize the cultivation of Wharton jelly-derived mesenchyma stem cells (WJ-MSCs) using physiological oxygen concentrations, and to compare the effect of “hypoxic” gas mixtures, based on nitrogen and argon, on their proliferative activity. Methods. From the first passage, WJ-MSCs were cultivated during five passages in the nitrogen-based gas mixture (3 % oxygen, 4 % carbon dioxide, 93 % nitrogen) and argon-based gas mixture (3 % oxygen, 4 % carbon dioxide, 93 % argon), 7 days before replating. At each passage the final cell number was estimated and the number of population doublings was calculated. Results. The proliferation level of WJ-MSCs, cultured in both gas mixtures with 3 % of O2, was significantly higher compared to that under the regular CO2-incubator conditions. In argon-based mixture, the WJ-MSCs proliferation was higher than in the control but lower than in nitrogen-based mixture. Conclusion. Cultivation of human WJ-MSCs under 3 % O2 had a stimulating effect on the cell proliferation potential. The highest intensity of the cell multiplication was observed in the nitrogen-based mixtures. Мета. Оптимізувати культивування і порівняти вплив газових сумішей зі зниженим вмістом кисню, на основі азоту та аргону, на процеси проліферації в культурах мезенхімальних стовбурових клітин Вартонового студню (МСК-ВС). Методи. Протягом 5 пасажів. МСК-ВС культивували в газових сумішах на основі азоту (кисень – 3 %, вуглекислий газ – 4 %, азот – 93 %) та аргону (кисень – 3 %, вуглекислий газ – 4 %, аргон – 93 %). На кожному пасажі після 7 днів культивування підраховували кількість клітин, і визначали число подвоєнь культури. Результати. Чисельність клітин МСК-ВС, культивованих в сумішах, що містять 3 % кисню, була вищою, ніж в загальноприйнятих умовах СО2-інкубатора. Рівень проліферації в суміші на основі аргону був нижчим, ніж в суміші на основі азоту, при цьому будучи вищим за такий для контрольних груп. Висновки. Культивування в газових сумішах, що містять 3 % кисню, мало стимулюючий вплив на процеси проліферації МСК-ВС. Найбільш високий рівень мультиплікації спостерігали в сумішах на основі азоту. Цель. Оптимизировать культивирование и сравнить влияния газовых смесей с пониженным содержанием кислорода на основе азота и аргона на процессы пролиферации в культурах мезенхимальных стволовых клеток Вартонова студня (МСК-ВС). Методы. На протяжении 5 пассажей. МСК-ВС культивировали в газовых смесях на основе азота (кислород – 3 %, углекислый газ – 4 %, азот – 93 %) и аргона (кислород – 3 %, углекислый газ – 4 %, аргон – 93 %). На каждом пассаже после 7 дней культивирования подсчитывали количество клеток, и определяли число удвоений культуры. Результаты. Численность клеток МСК-ВС, культивированных в смесях, содержащих 3 % кислорода, была выше, чем в общепринятых условиях СО2-инкубатора. Уровень пролиферации в смеси на основе аргона был несколько ниже, чем в смеси на основе азота, при этом будучи выше такого показателя для контрольных групп. Выводы. Культивирование в газовых смесях, содержащих 3 % кислорода, оказывало стимулирующее влияние на процессы пролиферации МСК-ВС. Наиболее высокий уровень мультипликации наблюдали в смесях на основе азота.